2021
DOI: 10.1192/bja.2021.55
|View full text |Cite
|
Sign up to set email alerts
|

The neuropsychiatric effects of nitrous oxide and low vitamin B12

Abstract: SUMMARY This narrative review article aims to update knowledge on the neuropsychiatric complications of nitrous oxide use and low vitamin B12. We consider common forms and uses of nitrous oxide (N2O) and review its mechanism of action, and then explore the potential impacts of use. In particular, neuropsychiatric effects mediated by low vitamin B12 are considered and the correct interpretation of laboratory results explored. This is of particular importance as where vitamin B12 is inactivated by chronic nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Nitrous oxide (N 2 O) abuse by individuals, disabling the function of B12, has been commonly associated with psychosis [141]. Sethi et al [143] reported on a case of abuse of N 2 O, causing functional B12 deficiency and psychosis, wherein treatment with B12 was effective. Farmer et al [144] reviewed the effects of N 2 O abuse on CNS function, and summarize treatment recommendations.…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Deficiency...mentioning
confidence: 99%
“…Nitrous oxide (N 2 O) abuse by individuals, disabling the function of B12, has been commonly associated with psychosis [141]. Sethi et al [143] reported on a case of abuse of N 2 O, causing functional B12 deficiency and psychosis, wherein treatment with B12 was effective. Farmer et al [144] reviewed the effects of N 2 O abuse on CNS function, and summarize treatment recommendations.…”
Section: Dysregulation Of the Folate Cycle With Psychosis: Deficiency...mentioning
confidence: 99%